A Conceptualization of Online Collaborative English Learning for Undergraduate Students in the New Normal Post Covid-19 Era - Yuli Marlina; Cahyono Cahyono (STAI Miftahul Ula Nganjuk, 2022)
Changing the way of learning process during the pandemic have made a point to find an appropriate approach in online leaning. This study aims to analyze language learning process in the first year of the pandemic, where the language needs a practice in the process of learning. In other words, language learning really requires direct interaction, this condition is added that not all colleges are ready for online learning either through LMS or other online forms which are already familiar by offline interactions. This study uses qualitative descriptive with deeply observations during the classes, and used the diffusion of innovation by Rogers which consists on stages of innovation. The research found the conceptualization of learning through online-collaborative, and using the online collaborative exam between groups has proven the willingness in interactive e-learning language and to be able to improve the competence of language skills, both listening, writing, reading, and speaking which are needed in the language process of university students whose vocabulary and English are still unfamiliar used in the introduction in each course in Indonesia